1989
DOI: 10.1590/s0101-81751989000100016
|View full text |Cite
|
Sign up to set email alerts
|

Ucides cordatus cordatus (Linnaeus, 1763) (Crustacea, Decapoda): complete larval development under laboratory conditions and its systematic position

Abstract: Misael Domingues Rodrigues 2Nilton José Hebling 3Six zoeal stages and the megalopa of the comestible crab Ucides cordatus cordatus (Linnaeus, 1763) are described and illustrated. The larvae were reared in the laboratory at temperature 25 ± lOC and water salinity of 24 0 /00; duration of stages and survival rates were measured. Comparisons with the descriptions of the zoeal morphologic characters of Ocypodidae and Gecarcinidae perrnited to include definitively U. c. cordatus in the family Ocypodidae, subfarni1y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2
15

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 15 publications
0
11
2
15
Order By: Relevance
“…The description of U. cordatus by RODRIGUES & HEBLING (1989) does not differ much from that in the present study. The former did not report the presence of a single seta on the antennule and a small lateral spine on each furca, which also have serrated margins (Table VI).…”
Section: Discussioncontrasting
confidence: 59%
“…The description of U. cordatus by RODRIGUES & HEBLING (1989) does not differ much from that in the present study. The former did not report the presence of a single seta on the antennule and a small lateral spine on each furca, which also have serrated margins (Table VI).…”
Section: Discussioncontrasting
confidence: 59%
“…Adult and juveniles survive long exposures to freshwater (> 3 weeks, Diele, unpublished), but the salinity tolerance of the larvae is not well known. In south-western Brazil Rodriguez and Hebling (1989) cultivated larvae in water with a constant salinity of 24. Survival from hatching to megalopa was 75% and the development comprised 5 to 6 zoeal stages.…”
Section: Introductionmentioning
confidence: 99%
“…These periods were considerably longer than the duration of the megalopa stage in the present study, which averaged 12.6 days. The main methodological difference between the present study and that of Rodrigues and Hebling (1989) was the presence of the mangrove sediment within the experimental container. The physicochemical characteristics of the substrates might strongly modulate the decapod metamorphosis, such as temperature (Jamieson and Phillips, 1993;McMillan et al, 1995;Anger et al, 2004), salinity (Islam et al, 2005), and conspecific chemical cues (Harvey, 1996;O'Connor and Judge, 1997;Gebauer et al, 1998;Rodríguez and Epifanio, 2000;Gebauer et al, 2002).…”
Section: Discussionmentioning
confidence: 63%
“…Thus, the present results suggested that the release of the megalopae on the sixth day from their molt might increase the survivorship of these larvae under natural conditions. The duration of the megalopal stage in U. cordatus has been reported by Rodrigues and Hebling (1989) to last from 55 to 61 days if the megalopae originated from Zoeae V, and from 43 to 69 days, if originated from Zoeae VI. These periods were considerably longer than the duration of the megalopa stage in the present study, which averaged 12.6 days.…”
Section: Discussionmentioning
confidence: 99%